Different Relationships between FENO and COPD Characteristics in Smokers and Ex-Smokers. (4th July 2019) - Högman, M.; Thornadtsson, A.; Bröms, K.; Janson, C.; Lisspers, K.; Ställberg, B.; Hedenström, H.; Malinovschi, A.
Abstract: Exhaled nitric oxide (FE NO) is a marker of type-2 inflammation in asthma and is used in its management. However, smokers and ex-smokers have lower FE NO values, and the clinical use of FE NO values in COPD patients is unclear. Therefore, we investigated if FE NO had a relationship to different COPD characteristics in smoking and ex-smoking subjects. Patients with COPD ( n = 533, 58% females) were investigated while in stable condition. Measurements of FE NO50, blood cell counts, IgE sensitisation and lung function were performed. Medication reconciliation was used to establish medication usage. Smokers ( n = 150) had lower FE NO50 9 (8, 10) ppb (geometric mean, 95% confidence interval) than ex-smokers did ( n = 383) 15 (14, 16) ppb, p < 0.001. FE NO50 was not associated with blood eosinophil or neutrophil levels in smokers, but in ex-smokers significant associations were found ( r = 0.23, p < 0.001) and ( r = –0.18, p = 0.001), respectively. Lower FE NO values were associated with lower FEV1 % predicted in both smokers ( r = 0.17, p = 0.040) and ex-smokers ( r = 0.20, p < 0.001). Neither the smokers nor ex-smokers with reported asthma or IgE sensitisation were linked to an increase in FE NO50 . Ex-smokers treated with inhaled corticosteroids (ICS) had lower FE NO50 14 (13, 15) ppb than non-treated ex-smokers 17 (15, 19) ppb, p = 0.024. This was not found in smokers ( p = 0.325). FE NO is associated with eosinophil inflammation and the use of ICS in ex-smoking COPD subjects, but not in smoking subjects suggesting that the value of FE NO as an inflammatory marker is more limited in smoking subjects. The association found between low FE NO values and low lung function requires further investigation.